Optimised an active anti-roll bar system using composite nonlinear feedback-linear quadratic gaussian controller - Noraishikin Zulkarnain, 1988-, author; Hairi Zamzuri, supervisor; Sekolah Razak UTM dalam Kejuruteraan dan Teknologi Termaju (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2016)
Thesis (Ph.D) - Universiti Teknologi Malaysia, 2016